Ultrasonic-assissted chemical synthesis of silver nanoparticles in Tamarind seed polyssaccharide and antibacterial efficacy against Vibrio natriegens. - Cuevas, Gabrielle Troy Albano (2012.)
Silver nanoparticles are highly unstable that cannot exist in nature for a very long period time. The silver nanoparticles were synthesized by ethanol reduction method, with the aid of ultrasonic agitation and tamarind seed polysaccharide was used as a stabilizing agent in the synthesis. The optimum conditions for the synthesis of silver nanoparticles was using 0.01001 M AgNO3, 800 mg/L Tamarind seed polysaccahride solution at pH >_ 7 sonicated for 60 minutes. The results of the study showed that the synthesized silver nanoparticles exhibited a maximum absorption peak at 416-434 nm in the visible spectrum. The color of the synthesized silver nanoparticles was dark yellow indicating that silver ions were reduced to silver nanoparticles. The stability of the silver nanoparticles increased as the concentration of tamarind seed polysaccharide was increased. The absorbance of all the synthesized silver nanoparticles dispalys significant difference at 95 percent confidence interval. The silver nanoparticles exhibited zones of inhibition on the Vibrio natriegens with a mean diameter of 1.90 cm and showed significant difference against the Amoxicillin solution, positive control, (0.90 cm +- 0.10) at 95 percent confidence interval.
Thesis (Undergraduate, Bachelor of Science in Chemistry) College of Arts and Sciences, University of the Philippines Visayas, Miagao, Iloilo.
Keywords: Tamarined Seed; Vibrio natriegens